Caracterización de la conducta compulsiva en una señora de 42 años en época de pandemia - Izquierdo Arechúa, Jimmy Humberto (2020)
The present case study aims to explain the problem faced by a 42-year-old woman who has compulsive behaviors that cause her discomfort as a result of the COVID-19 pandemic, the same one that presented anxious symptoms, which was affecting significantly his life, generating problems on a personal, social and work level. Through various sessions in which different instruments and techniques were used to collect information such as the interview, medical history, psychometric tests, it was possible to obtain a diagnosis and at the same time verify possible cognitive distortions that the patient had. Therefore, a cognitive-behavioral approach is presented which, through the application of various techniques, achieves a significant decrease in the problem and helps the patient improve her quality of life.